2011
DOI: 10.1037/a0023585
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Internalized Racial Oppression Scale for Black individuals.

Abstract: This article describes the development and validation of the Internalized Racial Oppression Scale (IROS) for Black individuals in 2 studies using a total sample of 468 Black college students. The IROS is intended to measure the degree to which racial oppression is internalized and replicated by Black individuals in the United States. An exploratory factor analysis suggested a five-factor solution: Belief in the Biased Representation of History (BRH), Devaluation of the African Worldview and Motifs (DAW), Alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
81
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 44 publications
3
81
1
6
Order By: Relevance
“…It is noteworthy that the first quantitative measure for internalized racism—the Nadanolization Scale—was not published until Taylor and Grundy (), perhaps a reflection of how internalized racism has been neglected by psychology. However, what is perhaps a reflection of the recent surge in psychological interest in internalized racism is that—in just the last decade—there have been psychometrically developed scales to capture internalized racism as experienced by various groups, such as African Americans (Bailey et al., ), Asian Americans (Choi, Israel, & Maeda, ; Liao, ), Filipino Americans (David & Okazaki, ), Latinx (Hipolito‐Delgado, ), Puerto Ricans (Capielo et al., ), Ghanaians (Utsey et al, ), and even a general scale for use with all Peoples of Color (Campon & Carter, ). Although groups differ in their experiences of internalized racism (e.g., desiring straight hair is common among African Americans but not Filipinos, while desiring straighter/bridged noses is common among Filipinos but not African Americans), it is important to note that there are some consistent similarities such as feelings of inferiority, shame, or embarrassment; adopting American or Western standards of physical attractiveness (e.g., lighter skin tones); animosity toward other members of one's racial/ethnic group; and minimizing, tolerating, denying, and even justifying racism.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that the first quantitative measure for internalized racism—the Nadanolization Scale—was not published until Taylor and Grundy (), perhaps a reflection of how internalized racism has been neglected by psychology. However, what is perhaps a reflection of the recent surge in psychological interest in internalized racism is that—in just the last decade—there have been psychometrically developed scales to capture internalized racism as experienced by various groups, such as African Americans (Bailey et al., ), Asian Americans (Choi, Israel, & Maeda, ; Liao, ), Filipino Americans (David & Okazaki, ), Latinx (Hipolito‐Delgado, ), Puerto Ricans (Capielo et al., ), Ghanaians (Utsey et al, ), and even a general scale for use with all Peoples of Color (Campon & Carter, ). Although groups differ in their experiences of internalized racism (e.g., desiring straight hair is common among African Americans but not Filipinos, while desiring straighter/bridged noses is common among Filipinos but not African Americans), it is important to note that there are some consistent similarities such as feelings of inferiority, shame, or embarrassment; adopting American or Western standards of physical attractiveness (e.g., lighter skin tones); animosity toward other members of one's racial/ethnic group; and minimizing, tolerating, denying, and even justifying racism.…”
Section: Resultsmentioning
confidence: 99%
“…Internalized racism has been conceptualized as a modern, covert form of racism that causes African Americans to collude with their own racial oppression, devaluing their African American culture and heritage (Bailey, Chung, Williams, Singh, & Terrell, 2011;Speight, 2007).…”
Section: Internalized Racismmentioning
confidence: 99%
“…Later studies utilized measures of racial identity-''the significance and qualitative meaning that individuals attribute to being Black in their conceptualizations of self'' (Sellers & Shelton, 2003, p. 1080) as a means of assessing African American participants' internal self-hatred (Bailey et al, 2011). However, more recently, authors have argued that this psychological process may have numerous underlying aspects including internalizing negative racial stereotypes (e.g., African Americans are lazy) and desiring features considered to be more European (e.g., body size, facial features, and hair texture; Bailey et al, 2011;Townsend, Thomas, Neilands, & Jackson, 2010). For example, Bailey, Chung, Williams, Singh, and Terrell (2011) suggested that the operationalization of internalized racial oppression may include beliefs that Africans and African Americans have not made significant contributions to history, devaluation of one's African heritage, desiring physical modifications to achieve Eurocentric standards of attractiveness, Eurocentric hairstyles, and acceptance of negative stereotypes regarding African Americans.…”
Section: Internalized Racismmentioning
confidence: 99%
See 2 more Smart Citations